The Complexity to Support Civil Servant Performance As a Public Organization in Local Government: Bibliometric Analysis - Nolla Puspita Dewi; Elly Rumengan; Etty Sri Wahyuni (International Forum of Researchers and Lecturers, 2025)
The local government management system is expected to focus on increasing accountability and, at the same time, improving civil servant performance that is oriented toward outcomes. This research aims to conduct a bibliometric examination of local government civil servant performance. This study analyzed 439 articles published from 2013 until July 2022 in the Scopus database on civil servant performance in government. The VosViewer program was utilized in the process of analyzing to find results on the most contributing authors, the number of citations, areas, organizations, publications, and co-occurrences of keywords. These results could create new gaps in the research that will be conducted in the future. The result shows civil servant performance relies on appraisal and work environment improvement. A conducive environment fosters mutual assistance, open communication, and conflict resolution, ultimately improving employee performance and fostering better relationships. Also, performance analysis is crucial for public administration and the public sector.